Effectiveness of Blended Learning Model-Based on “Kutub al-Tis’ah” Application in Improving Students’ Critical Thinking in Hadith Study Courses - Channa, Lilik (Didaktika Religia, 2022)
This study compares the enhancement of students’ critical thinking abilities between those who utilise the Blended Learning model based on Kutub al-Tis’ah and those who adhere to a conventional learning methodology. A quasi-experimental method with purposive sampling was employed, with two classes from the Architecture Study Program at the State Islamic University of Sunan Ampel Surabaya in 2020/2021 serving as samples. The experimental group was instructed using the blended learning model, while the control group was taught using conventional methods. The results of the post-test demonstrated that the experimental class exhibited significantly higher scores (with an average of 90.32 and a variance of 6.799) than the control class (with an average of 65.81 and a variance of 5.872). The results of the statistical tests, including those for normality (Kolmogorov-Smirnov and Shapiro-Wilk) and homogeneity (Levene), demonstrated that the data from both groups were normally distributed and homogeneous. A p-value of 0.00, less than 0.05, indicated that the null hypothesis should be rejected, demonstrating that the blended learning model effectively enhances critical thinking skills in Hadith Studies courses.